A utilização de modelagem da informação da construção em empresas de arquitetura e engenharia de Belo Horizonte - Miguel Pereira Stehling (2012)
Building Information Modeling (BIM) is a technology that allows companies of the construction industry more safety, reliability, speed and quality. It is a technological option that can be done in implementing projects in order to reduce waste and optimize the use of materials, thus contributing to sustainable development. With BIM it is possible to manage technical documentation of buildings and maintain a system for information and communication between managers, designers, owners, engineers, contractors, architects, real estate asset managers, and other stakeholders in the process. By applying questionnaires and from interviews, it was carried out a study to identify the current condition of BIM usage by companies and professionals in Belo Horizonte. This research involved architects and engineers specialized in residential, commercial and industrial project. It was identified characteristics of designers, companies, tools, challenges, benefits and characteristics of the implementation process. It was concluded that the implementation of BIM in Belo Horizonte is more developed in industrial designs than in residential and commercial design. Designers and companies in the residential and commercial sector are engaged in the substitution process of the traditional 2D design to 3D parametric models, while designers in industrial sector are already deploying interoperability between models of different disciplines, which corresponds to a more advanced phase of implementation. Among the proposed improvements are suggestions to stimulating the spirit of collaboration and sharing ofknowledge between the working teams and also the implementation of BIM through the involvement of all disciplines from the earliest stages of project development.